Pemanfaatan Tes Bahasa Indonesia Sebagai Upaya Meningkatkan Kultur Belajar Siswa di Sekolah Menengah Atas Negeri 8 Pinrang - Ramly Ramly; Muhammad Alfian Tuflih (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. The purpose of community service at Sekolah Menengah Negeri 8 Pinrang is to improve a positive learning culture for students by optimizing the utilization of tests as a learning resource. Considering the covid-19 pandemic, this community service activity involves a group of ten students to be a strategic target that is expected to expand the reach of the denomination of their results. Discussions, brainstorming, and training has succeeded in improving motivation and mastery of the substance of concepts as well as the skills of managing students' learning resources. It is concluded that the community's advocacy has succeeded in creating a learning culture for the target group.